Purification, characterization and larvicidal activity of a potent bioactive compound asarone from leaves of Acorus calamus against the culician larval mosquitoes. (October 2022) - Nithya, Kirubakaran; Bhuvaragavan, Sreeramulu; Sruthi, Kannan; Meenakumari, Mani; Shanthi, Sathappan; Janarthanan, Sundaram
Abstract: Mosquitoes are potent vectors by serving as agents to life-threatening diseases in humans. Increasing resistance in mosquitoes against existing insecticides and repellents brings new challenges and an opportunity to explore sustainable compounds. We chose six medicinal plants to screen potential bioactive compounds that could act as an insecticide. Among these, crude hexane leaf extract of Acorus calamus showed higher mortality percentage against Aedes aegypti and Culex quinquefasciatus . The LC50 and LC90 values were 151.86 ppm and 536.36 ppm, respectively, for the third instar A. aegypti larvae, and 174.70 ppm and 696.73 ppm, respectively, for C. quinquefasciatus . The treated larvae of both species showed morphological and physiological variations when compared to control. The GC–MS profile of purified fractions showed a single peak. Further, FT-IR and NMR analyses confirmed the propensity of the purified compound as trans asarone (phenylpropanoid; C12 H16 O3 . LC50 and LC90 values of purified asasone-treated larvae were 2.35 ppm and 12.58 ppm, respectively, for A. aegypti and 2.15 ppm and 11.58 ppm, respectively, for C. quinquefasciatus . Treatment of different sub-lethal doses of asarone to mosquito larvae at various time intervals showed disruption of intestinal layers. By showing negligible toxicity to non-target organism, purified asarone has a great potential in vector management. Graphical abstract: Unlabelled Image Highlights: Bioactive compound asarone was isolated from hexane leaf extract of A. calamus. The compound exhibited potent larvicidal activity against mosquito larvae. The treated larvae showed behavioural, morphological and histological changes. The asarone has completely disrupted the gut region of larvae.